ASSESSING THE EFFECTS OF CUSTOMER SATISFACTION AND RETENTION IN THE HOSPITALITY INDUSTRY: A STUDY OF ST. JACOBS AND GROOVY HOTELS, AKURE, ONDO STATE, NIGERIA - Ojo, Idowu (International Journal of Research -GRANTHAALAYAH, 2024)
This study looked into the effects of customer satisfaction and retention in the hospitality industry, a case study of St. Jacobs and Groovy Hotels in Akure, Ondo State. Meeting the needs of consumers makes it possible to retain them and promote customer retention, which guarantees continued business. To some extent, the accomplishment of corporate goals is determined by the degree of customer happiness and retention. For this study, a descriptive survey research design was adopted. Convenience sampling was used to choose the 120 customers that made up the study sample. The questionnaire served as a key data collection tool. Both descriptive and inferential statistics were used to analyze the data that were gathered. Bar charts and basic percentages were used to assess the respondents’ demographic data. The study employed Linear Regression Analysis and Pearson Correlation to evaluate the three hypotheses at significance levels of 0.05 alpha. Customer satisfaction is positively and significantly impacted by service quality, according to the results of the hypothesis tested. There is a significant relationship between customer satisfaction and client retention and the study indicated that customer care, customer satisfaction, and customer retention are positively and significantly correlated. This study suggested that, in order to provide customers with a sense of belonging, prompt and appropriate care should be provided whenever objections are expressed. Thus, it would be beneficial to look at additional factors related to the concept of customer happiness, such as the caliber and service of food and beverages, hotel branding, cleanliness, and security.